A stable and ultrafast K ion storage anode based on phase-engineered MoSe2. Issue 32 (22nd March 2021) - Liu, Lei; Xu, Jie; Sun, Jinmeng; He, Song; Wang, Ke; Chen, Yanan; Dou, Shuming; Du, Zhuzhu; Du, Hongfang; Ai, Wei; Huang, Wei
Abstract : A hybrid 1T/2H phase MoSe2 has been prepared by functionalized carbon substrate induced phase engineering, which enables boosted pseudocapacitive response and fast kinetics for K storage. Abstract : Potassium-ion batteries (PIBs) are attracting increasing attention due to the abundance of K resources, but the sluggish kinetics and inferior cycling stability of anodes still hinder their application. Herein, we present a hybrid 1T/2H phase MoSe2 anode, which shows noticeable pseudocapacitive response and fast kinetics for K storage. Correspondingly, superior electrochemical performances including a high reversible capacity of 440 mA h g −1 after 100 cycles at 0.1 A g −1 and superb rate capacity of 211 mA h g −1 at 20.0 A g −1 are achieved. We believe this work may shed light on the phase engineering of transition metal compounds for rapid charging PIBs.